2012
DOI: 10.2478/v10247-012-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of psyllium seed

Abstract: A b s t r a c t. Physical properties ie dimensions, volume, surface area, sphericity, true density, porosity, angle of repose, terminal velocity, static and dynamic friction coefficients on plywood, stainless steel, glass and galvanized iron sheet, force required for initiating seed rupture in horizontal and vertical orientations of psyllium seed at a moisture content of 7.2% (w.b.) were determined.K e y w o r d s: psyllium seed, physical properties, postharvest technology INTRODUCTION Psyllium (Plantago ovata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
3
18
0
1
Order By: Relevance
“…Sapota fruit showed the highest static coefficient of friction on plywood (0.31). A similar result was also reported by Davies and Zibokere (2011) for gbafilo fruit and by Ahmadi (2012) for psyllium seed. These properties are the key elements for calculation of compressibility and flow behaviour of materials used for designing storage structures.…”
Section: Resultssupporting
confidence: 89%
“…Sapota fruit showed the highest static coefficient of friction on plywood (0.31). A similar result was also reported by Davies and Zibokere (2011) for gbafilo fruit and by Ahmadi (2012) for psyllium seed. These properties are the key elements for calculation of compressibility and flow behaviour of materials used for designing storage structures.…”
Section: Resultssupporting
confidence: 89%
“…At the moisture content of 9.3% d.b. the terminal velocity of bitter gourd seed was found to be smaller than that of moth gram (Nimkar et al, 2005), mung bean (Unal et al, 2008), and Christmas Lima bean (Aghkhani et al, 2012), while it was greater than that of psyllium seed (Ahmadi et al, 2012). Experimental data of the static coefficient of friction for bitter gourd seed on frictional surfaces of rubber, plywood, aluminum, and galvanized iron sheet at various moisture levels are presented against the moisture content, as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…9 Studies have also shown that various factors, such as ionic power, protein-polysaccharide ratio, pH and nal concentration of the product, have signicant effects on the physico-chemical properties of protein-polysaccharide mixed systems. [22][23][24] Askari et al 22 by extracting psyllium seed hydrocolloid (PSH) and evaluating its rheological properties demonstrated that the rheological behavior is watery with shearing. 17,18 The seed husk contains high amounts of hydrocolloids, which can be obtained by separating the outer layer of grains by grinding or scratching, and they form approximately 25% of the whole grain.…”
Section: Introductionmentioning
confidence: 99%